2002
DOI: 10.1007/s00406-002-0379-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy of attention deficit hyperactivity disorder in adults

Abstract: In clinical practice many adult patients with attention deficit hyperactivity disorder (ADHD) ask for an additional psychotherapeutic intervention besides the medical therapy. In this paper we present a structured skill training program particularly tailored for adult patients with ADHD. The program is based on the principles of cognitive-behavioral treatment for borderline personality disorder developed by M. Linehan. It was modified to suit the special needs of adult patients with ADHD. In this exploratory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(122 citation statements)
references
References 18 publications
2
110
1
6
Order By: Relevance
“…CBT also incorporates cognitive modification strategies that assist the patient in identifying automatic thoughts, recognizing the ensuing feelings and behaviors that lead to maladaptive responses, and in reframing and problem solving to devise and implement more adaptive behaviors. Several studies have shown the efficacy of CBT in improving ADHD symptoms [89][90][91][92], organizational skills [91], depression and anxiety [89] in patients with ADHD. Research is needed to determine whether the incorporation of CBT strategies for ADHD into a behavioral weight loss program would improve both ADHD symptoms and weight loss.…”
Section: Exercisementioning
confidence: 99%
“…CBT also incorporates cognitive modification strategies that assist the patient in identifying automatic thoughts, recognizing the ensuing feelings and behaviors that lead to maladaptive responses, and in reframing and problem solving to devise and implement more adaptive behaviors. Several studies have shown the efficacy of CBT in improving ADHD symptoms [89][90][91][92], organizational skills [91], depression and anxiety [89] in patients with ADHD. Research is needed to determine whether the incorporation of CBT strategies for ADHD into a behavioral weight loss program would improve both ADHD symptoms and weight loss.…”
Section: Exercisementioning
confidence: 99%
“…In beiden Studien wird eine Reduktion der ADHS-Symptomatik, von psychischen Begleitstörungen sowie eine Verbesserung des Gesamtbefindens und der Selbstakzeptanz beschrieben, wobei von den Teilnehmern als wirksame Faktoren die Gruppensituation, die Informationsvermittlung und das Einüben störungsrelevanter Fertigkeiten eingeschätzt wurde [104]. …”
Section: Off-label-indikationunclassified
“…Dialectical behavior therapy (DBT) is a modern, structured, and goal-oriented therapeutic method whose efficacy has been proved successful on a number of psychological disorders such as borderline personality disorders, eating disorders [17], abuse substance [18], adolescents with ADHD [19], depression [20], and pervasive development disorders [21]. Currently, DBT has been used in physiologicalpsychological illnesses and shown hopeful results [22].…”
Section: Introductionmentioning
confidence: 99%